A comparison of snack serving sizes to USDA guidelines in healthy weight and overweight minority preschool children enrolled in Head Start. Issue 1 (December 2016) - Charvet, Andrea; Brogan Hartlieb, Kathryn; Yeh, Yulyu; Jen, K.-L.
Abstract Background Obesity disproportionately affects children from low-income families and those from racial and ethnic minorities. The relationship between snacking and weight status remains unclear, although snacking is known to be an important eating episode for energy and nutrient intake particularly in young children. The purpose of this pilot study was to examine the snack intake of minority preschool children enrolled in the Head Start Program in four centers in Detroit, Michigan, and investigate differences by child weight status. Methods This secondary data analysis used snack time food observation and anthropometric data from a convenience sample of 55 African American children (44 % girls, mean age = 3.8 years). Snack intake data was obtained over a mean of 5 days through direct observation of children by dietetic interns, and later converted into food group servings according to the United States Department of Agriculture (USDA) meal patterns and averaged for each child. Height and weight measurements were systematically collected and BMI-for-age percentiles were used to classify children into weight categories. One sample, paired samples and independent samplest -tests were performed to test for differences within and between means. Results Based on BMI-for-age percentiles, 72.7 % of the sample was under/healthy weight and 27.3 % was overweight/obese. Average (mean ± SD) intake of milk (0.76 ± 0.34) and overall fruits/vegetables (0.77 ± 0.34) was significantly lower than one USDA serving, while average intake of grains and breads (2.04 ± 0.89), meat/meat alternates (2.20 ± 1.89) and other foods (1.43 ± 1.08) was significantly higher than one USDA serving (p ≤ 0.05). Children ate more when offered canned versus fresh fruits (0.93 ± 0.57 vs. 0.65 ± 0.37, p = 0.007). Except for a significantly higher milk intake in the overweight/obese group compared to the under/healthy weight group (0.86 ± 0.48 vs. 0.72 ± 0.27, p = 0.021], no relationship was found between snack food intake and weight category. Only in the overweight/obese group was the intake of milk and fresh fruits not significantly different than one USDA serving. Conclusions Findings suggest that regardless of weight status low-income minority preschool children are consuming larger serving sizes when offered less healthy versus healthier snack foods. Continued efforts should be made to provide healthful snack foods at preschool settings to prevent obesity and promote healthier food habits.